Eksplorasi Penerapan Strategi Metakognitif dalam Pembelajaran Membaca Kritis di SMAN 1 Paiton: Exploration of Metacognitive Strategy Implementation in Critical Reading Learning at SMAN 1 Paiton - Hernika, Hernika; Aziz Wahab, Abdul; Haryas Harja Susetya, Hemas (Universitas Tidar, 2025)
This study aims to explore the application of metacognitive strategies in learning critical reading among grade X students at SMAN 1 Paiton. Metacognitive strategies include three main stages, namely planning, monitoring, and evaluating, which aim to help students realize their thinking process during reading. The method used in this research is descriptive qualitative with data collection techniques in the form of observation, interviews, and documentation. The results showed that the application of metacognitive strategies was able to improve students' critical reading skills, marked by an increase in students' ability to understand text structure, evaluate arguments, and reflect on the reading process. Students' responses to this strategy were also positive; they felt helped in understanding the text more deeply and became more active in the learning process. This study recommends metacognitive strategies as an effective approach to improve critical literacy skills at the secondary school level.